2003
DOI: 10.1017/s0952523803202066
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of GAD-65 and GAD-67 with tyrosine hydroxylase and nitric oxide synthase in amacrine and interplexiform cells of the primate, Cebus apella

Abstract: The expression of glutamate decarboxylase forms, GAD-65 and GAD-67, in GABAergic cells was studied by immunocytochemistry in the retina of the New World monkey, Cebus apella. In the innermost rows of the inner nuclear layer (INL), somata that express GABA correspond to about 45% of the total number of cells in the central retina and about 25% on the periphery. Three subsets of GABAergic amacrine cells were identified along the horizontal meridian: about 5% express only GAD-65 and 40% GAD-67, and approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 52 publications
3
11
1
Order By: Relevance
“…By contrast with the reported co‐localization of TH and GABA in the monkey, cat and mouse (Wässle & Chun 1988; Haverkamp & Wässle 2000; Andrade da Costa & Hoko 2003), there was no co‐localization between TH and GFP in our study. This might reflect the fact that the GFP in our mouse model was related to GAD67.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…By contrast with the reported co‐localization of TH and GABA in the monkey, cat and mouse (Wässle & Chun 1988; Haverkamp & Wässle 2000; Andrade da Costa & Hoko 2003), there was no co‐localization between TH and GFP in our study. This might reflect the fact that the GFP in our mouse model was related to GAD67.…”
Section: Discussioncontrasting
confidence: 99%
“…1998; Haverkamp et al. 2000; Andrade da Costa & Hoko 2003). We were able to confirm this finding in the mouse.…”
Section: Discussionmentioning
confidence: 99%
“…GAD65 and 67 are the two isoforms of the enzyme glutamate decarboxylase, which catalyzes the decarboxylation of glutamate to GABA in the retina [32], [48], [49]. It has been reported that in mammalian retinas, the GABAergic amacrine cells can express either or both GAD isoforms [49], [50]. Using an antibody that recognizes both GAD isoforms, we have shown in the present work that CRB3 colocalizes with most GAD65/67 processes.…”
Section: Discussionsupporting
confidence: 63%
“…This result confirms that bNOS, ChAT, GAD, and glycine are reliable AC markers in the GCL. We also observed that bNOS-IR was mostly colocalized with GABA-IR, which is in line with previous studies [51][52][53] In contrast, GCs and ACs were both found to accumulate 5-HT, and these cells resided in either the GCL or INL. Thus, GCs and ACs cannot be distinguished by observation of 5-HT accumulation.…”
Section: Glycine Chat Bnos and Gad Are Reliable Ac Markers In The supporting
confidence: 92%